Do Accounting Benefits of ERP Systems Impact the Satisfaction of End-Users? From the Perspective of Accountants and Internal Auditors in Sri Lanka - Dulshan Karunarathna; Samitha Rajapaksha (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- What are the accounting benefits perceived by accountants and internal auditors that entail through Enterprise Resource Planning (ERP) systems? Is there an interaction of ERP accounting benefits with the accountants' and internal auditors' satisfaction level in using ERP systems? Motivation- Many organizations are implementing ERP systems extensively while sharing a common database and being real-time. Past scholars summon empirical studies on ERP's impact on accounting benefits and user satisfaction. Therefore, this study was conducted from accountants' and internal auditors' perspective as recent scholars shed light on the cruciality of these two groups' perceptions as key ERP users. Idea- This study examines the accounting benefits that entail through the adoption of ERP systems by Sri Lankan companies with regard to ERP user satisfaction from the perspective of accountants and internal auditors. Data- The data were collected from 38 accountants and 19 internal auditors across 24 companies that are implementing ERP systems for more than four years. Tools- A quantitative survey methodology is employed to draw empirical evidence. Findings- The findings confirm that organizational, operational (time), and IT accounting benefits derived from ERP systems significantly and positively influence ERP users' satisfaction. In contrast, operational accounting benefits (cost) received the lowest rating and did not significantly influence user satisfaction. Contribution- While these findings are valuable to accountants and internal auditors to better understand the ERP accounting benefits, ERP consultants and system providers also benefit from identifying ERP accounting features to uplift user satisfaction in developing countries.
Keywords: M41; 650; Enterprise Resource Planning (ERP) systems; accounting benefits; accountants and internal auditors; user satisfaction